IKLIM ORGANISASI DI DINAS TENAGA KERJA DAN TRANSMIGRASI PROVINSI SUMATERA BARAT - Elsa Mitra (Jurnal Bahana Manajemen Pendidikan, 2014)
This study aimed to describing abot organization climate of Dinas Tenaga Kerja dan Transmigrasi Provinsi Sumatera Barat. The research focus are talking about responsibility, warmth, foith, and freedom in Dinas Tenaga Kerja dan Transmigrasi Provinsi Sumatera Barat. The population of this research is all of civil servant on Dinas Tenaga Kerja dan Transmigrasi provinsi Sumatera Barat, and samples of this research 8 of civil servant in Dinas Tenaga Kerja dan Transigrasi Provinsi Sumatera Barat. Instrumen that used is questionnaire result of research by using average with responsibility 3,5, warmth 3,3, faith 3,6 and freedom 3,3. It’s mean organization climate of Dinas Tenaga Kerja dan Transmigrasi Provinsi Sumatera Barat is condusive. Key word : climate organization